Pemanfaatan Kelapa menjadi Produk Zero Waste untuk Menunjang Green Economy di Desa Asahduren, Kecamatan Pekutatan, Jembrana, Bali: Utilization of Coconut as a Zero Waste Product to Support the Green Economy in Asahduren Village, Pekutatan District, Jembrana, Bali - Suariani, Luh; Yudiastari, Ni Made; Singapurwa, Ni Made Ayu Suardani; Pranamya, I Agus Kerta; Naratama, I Putu Ngurah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Coconut is one of the superior products produced in Segah Hamlet, Asahduren Village, Jembrana Regency, Bali. The PM-UPUD program aims to strengthen the development of farmer groups and MSMEs to strengthen agriculture-based community empowerment and livestock. Its operational methods include research, consultation, direct practice, monitoring, and evaluation. The farmer group of PM-UPUD partners is the Kusuma Farmer Women Group based in Segah Hamlet. The challenges faced by the partners include the production of traditional vegetable oil and the management of coconut pomace. Through PM-UPUD activities, farmer groups are equipped with the capacity and skills to produce oil waste and process coconut pulp into animal feed and processed food in an integrated and comprehensive manner. Farmers can create better quality tandusan oil and process coconut pulp into animal feed and processed food. PM-UPUD activities can increase income and improve the welfare of the community, especially members of coconut producer groups.